2023
DOI: 10.20344/amp.18888
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de Risco para Alta Prorrogada por Motivos Sociais: Um Estudo Retrospectivo

Abstract: Introdução: Os hospitais deparam-se com uma percentagem das suas camas ocupadas por doentes cuja alta hospitalar está limitada não pela alta clínica, mas por outros fatores. Cria-se a necessidade da identificação precoce dos indivíduos que estão em risco de uma alta prorrogada por motivos sociais (internamentos sociais - IS), de forma a reduzir gastos e a acrescentar valor que se traduza em saúde dos utentes. O objetivo deste estudo foi identificar os fatores de risco demográficos e clínicos que condicionam ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In the same way, participants claimed to rarely or never present non-clinical complaints while attending health appointments, which was a surprising result because data suggests that one in five appointments with general practitioners can be linked to unmet social needs ( Zantinge et al, 2005 ). To our knowledge there is currently no equivalent data available in Portugal, but a recent study showed that one in five patients remained hospitalized after clinical discharge due to social factors (e.g, inadequate family support) ( Martins et al, 2023 ). Thus, it is possible that participants did not recall their appointments accurately or it could be that they believe doctors are disinterested in those subjects; further examination is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, participants claimed to rarely or never present non-clinical complaints while attending health appointments, which was a surprising result because data suggests that one in five appointments with general practitioners can be linked to unmet social needs ( Zantinge et al, 2005 ). To our knowledge there is currently no equivalent data available in Portugal, but a recent study showed that one in five patients remained hospitalized after clinical discharge due to social factors (e.g, inadequate family support) ( Martins et al, 2023 ). Thus, it is possible that participants did not recall their appointments accurately or it could be that they believe doctors are disinterested in those subjects; further examination is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This work is a single-center observational study focused on a limited number of wards, whose common denominator is given by the fact that they mostly admit their patients from the same population, and with non-surgical necessities. While the organization of SSP hospital within ASL Roma 1 may be peculiar, its difficulties in the discharge process are not, as they are worldwide encountered [ 22 , 81 , 82 ]. A recent work of Manning and Islam highlighted that most of the challenges in patient flow management are not directly related to clinical situation, and solution must be found at organizational level [ 83 ].…”
Section: Discussionmentioning
confidence: 99%